SOIL EROSION ASSESMENT IN SOUTHERN EVIA ISLAND USING USLE AND GIS - Bathrellos, G.D.; Skilodimou, H.D.; Chousianitis, K.G. (Bulletin of the Geological Society of Greece, 2010)
In the present study the evaluation of soil erosion in Southern Evia Island was carried out. Data related with precipitation, morphology, land cover and lithology were collected. A spatial database was created and the further processing of the collected data was prepared using GIS. The Universal Soil Loss Equation (USLE) was used to predict the spatial distribution of the average annual rate of erosion. Five major factors were used to calculate the soil loss. These are rainfall erositivity (R), soil erodibility (K), slope length and steepness (LS), cropping management (C) and conservation supporting practice (P). Each factor is the numerical estimate of a specific condition that affects the severity of soil erosion. The obtained soil loss values were used to create the erosion risk map. The applied methodology provides a cost effected and rapid estimation of areas that are vulnerable to soil erosion and need immediate attention from soil conservation point of view. Moreover these results can be used to assist land use planning.